KOMUNIKASI ANTARBUDAYA ETNIK JAWA DAN ETNIK KETURUNAN CINA - Aksan, Eka Ermita; Rochayanti, Christina; Sutrisno, Isbandi (Jurnal Ilmu Komunikasi, 2009)
Balong settlement at Surakarta is a portrait unique of settlement because there are Javanese and generation of China. They was could harmonies live and when racial unrest gen- eration of China at Surakarta, it settlement not touched by protester. Difference culture not problem but it applied color live them in settlement. Not reason for know each one to other. Intercultural communication in settlement live of society here as focus observation. Informant succeed dept interview as many as eight, four ethnic generation China and four Javanese. Intercultural communication composed dynamic communication between China and Java eth- nic. They used Javanese as language everyday, difference shake hands between man and women, difference flag or symbol when overtaken by death could understood between ethnic China and Javanese ethnic. China claim to be there’s cultural succeeded in uniting with java cultural. Social interaction China and Javanese looked in kinds of social activity like social gathering, fasting open together, village patrol, independent day celebration, and voluntary labor service, etc. Social activity is interaction social medium people in Balong settlement. When racial unrest of China at Surakarta fifth, Balong settlement safe in this town. There are tolerance very nice, care and familiar among people in village very nice, it communication generation China and Javanese effective.